2000
DOI: 10.1080/00071660086484
|View full text |Cite
|
Sign up to set email alerts
|

The effect of light intensity on growth and development of turkey toms

Abstract: 1. The effect of light intensities from 10 to 700 lux on the performance of 5 to 18 week-old turkey males was studied in 2 trials. 2. Body weight of 18 week-old turkeys, in both experiments, was highest under the lowest light intensity This coincided with higher weight gain and lower food intake, which resulted in significantly better food conversion efficiency 3. Light intensity affected heart muscle weight but not weight of breast muscle, abdominal fat or testis as proportions of body weight. 4. The decline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 37 publications
1
13
0
1
Order By: Relevance
“…The feed intake of turkeys exposed to a lighting program of 12L:12D seemed to follow a compensatory pattern in which they increased their feed intake resulting in increased weight gain as compared to that of turkeys receiving a lighting program of 23L:1D and 18L:6D. Though this finding is consistent with the results of HERSTAD (1992), NEWBERRY (1992), HULET et al (1993), CLASSEN et al (1994, HEMILTON and KENNIE (1997), SENGUL et al (2000), andYAHAV et al (2000), it provides other implications. In this regard, in addition to the trial conditions, the aim of studies and the use of statistical models for the evaluation of the results of such studies can have significant influence on the outcome of such studies.…”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…The feed intake of turkeys exposed to a lighting program of 12L:12D seemed to follow a compensatory pattern in which they increased their feed intake resulting in increased weight gain as compared to that of turkeys receiving a lighting program of 23L:1D and 18L:6D. Though this finding is consistent with the results of HERSTAD (1992), NEWBERRY (1992), HULET et al (1993), CLASSEN et al (1994, HEMILTON and KENNIE (1997), SENGUL et al (2000), andYAHAV et al (2000), it provides other implications. In this regard, in addition to the trial conditions, the aim of studies and the use of statistical models for the evaluation of the results of such studies can have significant influence on the outcome of such studies.…”
Section: Methodssupporting
confidence: 80%
“…Proper lighting program should be determined since the live weight of turkey varies according to the lighting program applied. Many studies have been carried out to determine the effect of different lighting systems on live weight gain and growth performance in poultry production (BUCKLAND et al, 1976;SIOPES et al, 1986;CECIL, 1986;HESTER et al, 1987;KOVACHISHKI et al, 1987;LEWIS and PERRY, 1990;AL-MAHROUS, 1997;YAHAV et al, 2000). However, convincing results have not been always obtained from these studies due to the aim of the study or the choice of the statistical methods in the evaluation of the data.…”
Section: Introductionmentioning
confidence: 86%
“…Light is consists of three different aspects: photoperiod, color and intensity (Lewis and Morris, 1998). There has been much workers focused on the effects of light intensity on different poultry species; laying hens (Lewis et al, 2004), broilers (Ahmad et al, 2011) and turkeys (Yahav et al, 2000) in different aspects such as: production (Lien et al, 2007), behaviour (Alvino et al, 2009), physiology (Lewis et al, 2005), vision (Prescott et al, 2003) and welfare (Deep et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Most researchers conducting broiler performance trials have assessed different light sources (Levenick and Leighton, 1988;Rozenboim et al, 1999), lighting periods (Downs et al, 2006;Schwean-Lardner et al, 2013), light intensities (Yahav et al, 2000;Lien et al, 2008), monochromatic light colors (Rozenboim et al, 2004;Cao et al, 2008;Ke et al, 2011) and combined light colors (Karakaya et al, 2009;Cao et al, 2012) on performance of broiler chickens. Rozenboim et al (2004) demonstrated that green (G) light stimulates growth of birds at an early age, and that shifting birds to a different light environment at 10 or 20 days of age may further stimulate growth.…”
Section: Introductionmentioning
confidence: 99%